EFEKTIVITAS ALAT PENUKAR KALOR PADA SISTEM PENDINGIN GENERATOR PLTA - Anwar, Khairil (MEKTEK, 2011)
This paper discuss about effectiveness of heat exchanger in the cooling system of hydropower generator.Data obtained from generator cooled PLTA at Sulewana, Poso. The type of heat exchanger is compact heatexchanger, with dimensions: : SL=0.021 m, SD=0.029 m, ST=0.04 m, L=1.5 m, DTubing=0.019m. The resultshows that air temperature continues to decrease after passing through the cooler. Air temperature duringthe first pass through to the cooler is 75Â°C and continues to decline as a generator that drives the movementof air through the cooler, and the cooling water continues to rise from the initial temperature of 28oC to34oC. While the effectiveness of heat exchanger, has increase due to deacreasing air temperature circulatedinside the generator by 37 %